Explanation :
Intially $ (\mathrm t=0^-) $ the inductor would be uncharged.
So, $ \mathrm I(0^+)=0 $
The KVL in the loop will be
$ \;\;\;\;\;\;\;\;\;\;\;\;\;\mathrm V=\mathrm{RI}+\mathrm L\frac{\mathrm{dI}}{\mathrm{dt}} $
At $ \mathrm t=0^+ $
$ \;\;\;\;\;\;\;\;\;\;\;\;\;\mathrm V=\mathrm{RI}(0^+)+\mathrm L\frac{\mathrm{dI}}{\mathrm{dt}}(0^+) $
since, $ \mathrm I(0^+)=0 $
So, $ \frac{\mathrm{dI}}{\mathrm{dt}}(0^+)+\frac{\mathrm V}{\mathrm L} $
Now, lets differentiate the above equation
So,$\frac{\mathrm{dV}}{\mathrm{dt}}=\mathrm{R}\frac{\mathrm{dI}}{\mathrm{dt}}+\mathrm{L}\frac{\mathrm{dI}}{{\mathrm{dt}}^{2}}$
$ \;\;\;\;\;\;\;0=\mathrm R\frac{\mathrm{dI}}{\mathrm{dt}}+\mathrm L\frac{\mathrm{dI}}{\mathrm{dt}^2} $
At $\mathrm{T}={0}^{+}$
$0=\mathrm{R}\frac{{\displaystyle \mathrm{dI}}}{{\displaystyle \mathrm{dt}}}\left({0}^{+}\right)+\mathrm{L}\frac{{\mathrm{dI}}^{2}}{{\mathrm{dt}}^{2}}\left({0}^{+}\right)$
So, $ \frac{\mathrm d^2\mathrm I}{\mathrm{dt}^2}(0^+)=\left\{-\frac{\mathrm R}{\mathrm L^2}.\mathrm V\right\} $